Effect of Loading Rate on Viscoelastic Behaviour of Cassava Roots (Manihot Esculenta Crantz) in Bending - Nwakuba, N. R.; Asoegwu, S. N.; Makanjuola, G. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The effect of loading rate on the viscoelastic response of cassava roots, at a moisture content of 52.13 ± 5.74% (w.b.), to applied bending forces was studied. Experiments were conducted using a modified Instron Testing Machine (ITM) of 1 kN capacity, to investigate both creep and stress relaxation (viscoelastic) behaviour of cassava roots (variety TME 419) when static bending forces were applied at mid-span with loading rates of 2.7, 4.2, 5.3, 7.45, and 9.9 mm min-1. The creep behaviour indicated that the creep compliance may be described using a 4-element model consisting of Maxwell and Kelvin models in series. The retardation time and the instantaneous creep compliance of cassava root were found to be 25.5 s and 0.03009 (N mm-2)-1, respectively. The stress relaxation behaviour could be represented using a 2-element Maxwell approach with a parallel-orientated spring. The relaxation times are 20 and 500 s, for the range of the loading rates. Relaxation modulus was found to be a function of the degree of loading, rising as the degree of loading intensified and decreasing with time. As the loading rate increased from 2.7 – 9.9 mm min-1, the relaxation modulus increased from 1.25 – 6.89 N mm-2. The result of this study gives an idea of the food product attributes vis-à-vis its strength characteristics to mechanical damage. It guides the food process engineer in estimating the impact of stress on cassava roots during postharvest operations for optimum design of efficient cassava peeling machines and product storage quality. Prospects for further work were stated.